The Representation of Literacy as Individualism in Greta Gerwig's Little Women (2019) - Mellyna Putri Diniar (Tell : Teaching of English Language and Literature Journal, 2023)
Literacy practice describes how people interact with text or use written language according to their values. There are several ways to express literacy, one of which is literacy as individualism (William & Zenger, 2007, p. 127). It primarily focuses on individuals' uniqueness and how it alienates them from people in general. This theory is in line with Greta Gerwig’s Little Women (2019), which features numerous events on literacy practices. The purpose of the study is to demonstrate how Jo March's individualism in Gerwig's Little Women (2019) is illustrated through literacy. The conceptual framework is based on the New Literacy Studies (NLS) perspective of literacy as a social practice as well as using Williams and Zenger's (2007, p. 127) theory of literacy as individualism. This study aims to illustrate how Jo March represents literacy as individualism. The study's conclusions ultimately show that Jo March's individualism can be reflected through literacy under her routines of reading books, writing short stories, composing a novel, and writing letters as well as receiving letters from her family in the film.